Pengaruh Pertumbuhan Ekonomi dan Kualitas Pendidikan terhadap Penyerapan Tenaga Kerja di Kabupaten/Kota Provinsi Jawa Barat - Shindi Widia; M Afdal Samsuddin (Moneter : Jurnal Ekonomi dan Keuangan, 2025)
This study aims to analyze the influence of economic growth and education quality on labor absorption in 27 regencies/cities of West Java Province during the 2020–2024 period using the Random Effect Model (REM) method. The estimation results show that economic growth has a positive and significant effect on labor absorption, with a coefficient of 0.322424 and a p-value of 0.0002. This indicates that regional economic growth contributes to increasing employment opportunities. On the other hand, the quality of education, measured by the average years of schooling, has a negative and insignificant effect on labor absorption, with a coefficient of -0.706782 and a p-value of 0.0755. These findings suggest that improvements in formal education do not automatically lead to increased labor absorption, likely due to a mismatch between graduate qualifications and labor market needs. The Adjusted R-squared value of 0.091650 indicates that the model explains only about 9.16% of the variation in labor absorption, with the remaining variation influenced by other unobserved factors. Therefore, strategic policies are needed, such as the development of labor-intensive sectors and the improvement of vocational education quality and relevance, to optimally enhance labor absorption in West Java.